2011
DOI: 10.2214/ajr.10.5937
|View full text |Cite
|
Sign up to set email alerts
|

New Vertebral Compression Fractures After Prophylactic Vertebroplasty in Osteoporotic Patients

Abstract: Patients with three or more fractures tended to have subsequent fractures, despite undergoing prophylactic percutaneous vertebroplasty. However, there was no increased risk of subsequent fractures related to prophylactic percutaneous vertebroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…[18,19] PVP can also increase the risk of fractures of adjacent vertebrae. [14,2023] The incidence of postoperative infections is low. [24] Systemic complications are rare, [25,26] but can produce serious diseases—fat embolism, [27] PMMA pulmonary embolism, [25,2830] cardiac damage, [31,32] or arterial [33] or renal embolization.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] PVP can also increase the risk of fractures of adjacent vertebrae. [14,2023] The incidence of postoperative infections is low. [24] Systemic complications are rare, [25,26] but can produce serious diseases—fat embolism, [27] PMMA pulmonary embolism, [25,2830] cardiac damage, [31,32] or arterial [33] or renal embolization.…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients may suffer subsequent fractures in the untreated vertebrae following vertebroplasty, which usually requires further treatment . Previous studies found that the incidence of subsequent VCFs ranged from 6.16 to 37% .…”
Section: Introductionmentioning
confidence: 99%
“…The osteoporotic vertebral compression fractures (OVCF) have attracted more and more attention due to increase in life span globally and aging population 12345. Vertebroplasty has gained popularity during the past few years for the treatment of osteoporotic compression fractures 6789.…”
Section: Introductionmentioning
confidence: 99%